Study on colour changes in appearances based on two drying process of Gigantochloa Scortechinii - Muhammad Yusrizalafiq Muhamad Yusri (2017)
This study investigated the colour changes of 2 and 4 years-old Gigantochloa scortechinii culms at different drying techniques. Parameters of drying techniques are open air dried and under shed air dried were taken in account as their influences in enhancing the colour changes of bamboo from outer and inner part of bamboo. The 2 year-old G.scortechinii culms were considered as young where the inner part of the culms would normally having lighter colour than at the outer part of the culms. Same goes with the 4 year-old G.scortechinii culms which were considered as matured. Turning this bamboo into panel and furniture at this stage will resulted in uneven colour as the results of the mixture between the outer and inner part of the bamboo. This will decrease the value of the products. To compare between both 2 and 4 years-old B. vulgaris culms, the colour at the outer part of 4 year-old culms were pale compared with 2 year-old that were brighter. The colour changes were measured by Minolta Chroma-METER CR-310 and the result presented based on CIE L*a*b* colour co-ordinates system. The result shows that the rising temperature at different drying techniques resulted in enhancing and darkening of bamboo tissues. The results show that the changes of colour are significance at year four. This show that 4 years old are better in making product.